2013
DOI: 10.1116/1.4843575
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocarbon assisted atomic layer etching of SiO2 using cyclic Ar/C4F8 plasma

Abstract: The authors demonstrate atomic layer etching of SiO 2 using a steady-state Ar plasma, periodic injection of a defined number of C 4 F 8 molecules, and synchronized plasma-based Ar þ ion bombardment. C 4 F 8 injection enables control of the deposited fluorocarbon (FC) layer thickness in the one to several Å ngstrom range and chemical modification of the SiO 2 surface. For low energy Ar þ ion bombardment conditions, the physical sputter rate of SiO 2 vanishes, whereas SiO 2 can be etched when FC reactants are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(109 citation statements)
references
References 21 publications
3
103
0
Order By: Relevance
“…38,39 These improved results were attributed to a low edge damage of the gate oxide during ALEt by maintaining the surface composition at the edge of the gate oxide together with exact control of the Si etch depth. Recently, Metzler et al 40 also demonstrated ALEt of SiO 2 using a steady-state Ar plasma, periodic injection of a defined amount of C 4 F 8 gas and synchronized plasma-based Ar + ion bombardment. Injecting a predefined amount of C 4 F 8 gas leads to the controlled deposition of a fluorocarbon (FC) layer in the one to several Ångstroms thickness range onto the SiO 2 surface.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
“…38,39 These improved results were attributed to a low edge damage of the gate oxide during ALEt by maintaining the surface composition at the edge of the gate oxide together with exact control of the Si etch depth. Recently, Metzler et al 40 also demonstrated ALEt of SiO 2 using a steady-state Ar plasma, periodic injection of a defined amount of C 4 F 8 gas and synchronized plasma-based Ar + ion bombardment. Injecting a predefined amount of C 4 F 8 gas leads to the controlled deposition of a fluorocarbon (FC) layer in the one to several Ångstroms thickness range onto the SiO 2 surface.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
“…as seen in the case of SiO 2 ALE. 9,95,99 Additionally, the somewhat relaxed expectations relative to true atomistic level control make the prospect of broad implementation more realistic.…”
Section: Issues and Needsmentioning
confidence: 99%
“…Example of thickness evolution during eight cycles of an SiO 2 ALE process. 99 which enables controlled removal of Angstrom-thick SiO 2 layers per cycle.…”
Section: Iii-v: Gaasmentioning
confidence: 99%
“…55 We conclude that today the potential of ALD-assisted nanomanufacturing technologies like Atomic Layer Etching (ALEt) concepts derived from etch-purge-passivation/deposition-purge subroutines in (D)RIE and ALD is now clearly being recognized and promoted. 10,54,56,[57][58][59] The ongoing scaling of Moore's Law will soon require the implemention of these complementary technologies to meet the 10-nm challenges in surface and sidewall passivation of resist and feature patterns that is required to minimize interface, line edge and fin wall roughness.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%